2020
DOI: 10.1002/lol2.10167
|View full text |Cite
|
Sign up to set email alerts
|

Do diatoms dominate benthic production in shallow systems? A case study from a mixed seagrass bed

Abstract: Diatoms are ubiquitous members of macrophyte beds. They are part of the water column community and are found in the benthos, in the sediment and as epiphytes. It is recognized that assemblages in these coastal habitats are highly productive, yet diatom contribution to production has not been quantified directly. We disentangled contributions of diatoms from other producers in a seagrass bed by employing a diatom inhibitor and measuring community production and respiration. We found that the contribution of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Chlorophyll a concentration in the first centimetre of the sediment ranged from 6 to 9 µg g -1 , equivalent to 43 to 59 mg m -2 . These values were in the range of concentrations measured in other coral reef sediments where sediments are net autotrophic and microphytobenthos has been shown to be a relevant primary producer in the benthic compartment (Heil et al, 2004;Hochard et al, 2012;Cox et al, 2020). Despite the similar biomass of microphytobenthos (based on the chlorophyll concentrations) suggesting certain relevance of the microphytobenthos biomass in the benthic compartment, our measurements showed that the sediment was net heterotrophic.…”
Section: Sediment Metabolismsupporting
confidence: 56%
“…Chlorophyll a concentration in the first centimetre of the sediment ranged from 6 to 9 µg g -1 , equivalent to 43 to 59 mg m -2 . These values were in the range of concentrations measured in other coral reef sediments where sediments are net autotrophic and microphytobenthos has been shown to be a relevant primary producer in the benthic compartment (Heil et al, 2004;Hochard et al, 2012;Cox et al, 2020). Despite the similar biomass of microphytobenthos (based on the chlorophyll concentrations) suggesting certain relevance of the microphytobenthos biomass in the benthic compartment, our measurements showed that the sediment was net heterotrophic.…”
Section: Sediment Metabolismsupporting
confidence: 56%
“…In addition to being primary drivers in the cycling of major nutrients globally, these photosynthetic microorganisms provide other essential ecological services in terms of sustainability of planktonic and benthic habitats. Their position at the base of the aquatic food chain results from the metabolic activity of their cells which make diatoms the food and energy source for numerous invertebrates, micro-and meiograzers, but also vertebrates, e.g., benthic fish [5]. This important role in the food chain is based on the fact that diatoms primary storage materials are triacylglycerols (TAGs, e.g., [6]) and carbohydrates (chrysolaminarin, e.g., [7]).…”
Section: Introductionmentioning
confidence: 99%
“…They play key roles in the sustainability of the littoral ecosystems (cf. Cox et al, 2020) including suspension feeders, thanks to their prominent place in the food web as primary producers (Houki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%